Participatory Communication for Equity of Access in the Management of Ketapang Aquaculture Ecotourism - Anam, Khairil; Abdurrahman, Ade Irfan; Pratama, Rizal Abdi; Amalia, Anisa (Nyimak: Journal of Communication, 2025)
This research is prompted by the reality that despite significant growth in Indonesia's tourism sector, the utilization of natural resources, especially in coastal areas, is still not fully optimized and is susceptible to corporate control, which can displace local communities. This situation is further complicated by issues of unequal access and power dynamics that hinder fair ecotourism management. The study's primary goal is to identify stakeholders and analyze the function of participatory communication in managing the Ketapang Urban Aquaculture (KUA) ecotourism site to ensure equitable access. Adopting a constructivist paradigm and a qualitative methodology, data was collected through a combination of in-depth interviews, Focus Group Discussions (FGDs), and direct field observations. The findings reveal that, while the KUA project has been successful in terms of physical development, significant gaps remain at the community level, including the absence of structured community development programs and a low level of environmental awareness. Participatory communication serves as a crucial tool for bridging the diverse interests of various parties and boosting community involvement, which has been shown to mitigate conflict and strengthen solidarity among stakeholders. Consequently, this research advocates for a more inclusive communication approach to enhance sustainable ecotourism management.Keywords: Participatory communication, local community, stakeholder analysis, ecotourism ABSTRAKRiset ini dilatarbelakangi oleh fakta bahwa meskipun sektor pariwisata Indonesia telah berkembang pesat, pemanfaatan sumber daya alam, khususnya di wilayah pesisir, masih belum optimal dan rentan terhadap dominasi korporasi yang dapat meminggirkan masyarakat lokal. Kondisi ini diperburuk oleh masalah ketidakadilan akses dan kekuasaan yang menghambat pengelolaan ekowisata yang adil. Penelitian ini bertujuan untuk memetakan pemangku kepentingan dan menganalisis peran komunikasi partisipatif dalam pengelolaan Ekowisata Ketapang Urban Aquaculture (KUA) untuk mewujudkan keadilan akses. Menggunakan paradigma konstruktivisme dan pendekatan kualitatif, data dikumpulkan melalui wawancara, FGD, dan observasi lapangan. Hasil penelitian menunjukkan bahwa meskipun proyek KUA berhasil mencapai pembangunan fisik, ada kesenjangan signifikan di tingkat komunitas, seperti kurangnya program pengembangan masyarakat dan rendahnya kesadaran lingkungan. Komunikasi partisipatif menjadi elemen utama untuk menjembatani kepentingan berbagai pihak dan meningkatkan partisipasi masyarakat, yang terbukti dapat mengurangi konflik dan memperkuat solidaritas antar pemangku kepentingan. Oleh karena itu, riset ini merekomendasikan strategi komunikasi yang lebih inklusif untuk perbaikan pengelolaan ekowisata yang berkelanjutan.Kata Kunci: Komunikasi partisipatif, komunitas lokal, analisis stakeholder, ekowisata